Estrategias metodológicas innovadoras y su relación con la deserción escolar en la unidad educativa “La Maná” de básica superior intensiva oferta extraordinaria para personas con escolaridad inconclusa (pcei), periodo lectivo 2021-2022 - Corrales Corrales, Linda Verónica (2022)
The educational development project proposes: Innovative methodological strategies and their relationship with school dropout in the "La Maná" Educational Unit of Basic Superior Intensive extraordinary offer for People with Unfinished Schooling (PCEI), 2021 2022 school period. It is essential that the school strengthen pedagogical practices and implement flexible methodological tools for the educational attention of young people and adults in a situation of unfinished schooling, strengthen learning, development of skills that allow improving academic performance and reducing the dropout rate. The main objective of the research is to develop innovative methodological strategies that reduce school dropout, establish pedagogical mechanisms to develop innovative, didactic, teaching-learning skills and actions, make pedagogical support effective, improve the quality of education, empower skills, capacities and achieve comprehensive training in the students of the “La Maná” Educational Unit of Basic Superior Intensive extraordinary offer. A qualitative quantitative approach was developed, to support this work, surveys and interviews were carried out, which demonstrate the interest of teachers and students in the development of innovative methodological strategies as a pedagogical tool to reduce school dropout.